(n + 1)! = (n + 1)n(n − 1)
given (n + 1)! = (n + 1)n!
∴ (n + 1)n! = (n + 1)n(n − 1)
given n! = n(n − 1)!
∴ (n + 1)n(n − 1)! = (n + 1)n(n − 1)
given (n − 1)! = (n − 1)(n − 2)!
∴ (n + 1)n(n − 1)(n − 2)! = (n + 1)n(n − 1)
∴ (n + 1)n(n − 1)(n − 2)! − (n + 1)n(n − 1) = 0
∴ (n + 1)n(n − 1)[(n − 2)! − 1] = 0
∴ n + 1 = 0, n = 0, n − 1 = 0 and (n − 2)! − 1 = 0
∴ n = -1, n = 0, n = 1 and (n − 2)! = 1
given 1! = 1 and 0! = 1
∴ n = -1, n = 0, n = 1, n − 2 = 1 and n − 2 = 0
∴ n = -1, n = 0, n = 1, n = 2 and n = 3
now factorials are only defined whole numbers not integers so in the original form of the equation tells n + 1 ≥ 0 and (n + 1)n(n − 1) ≥ 1
as n=-1,0 and 1 all make (n + 1)n(n − 1) ≥ 1 false they are not valid solutions
∴ n = 2 and n = 3
test
n = 3 then (n + 1)! = (n + 1)n(n − 1) is 4! = 4*3*2 is true.
n = 2 then (n + 1)! = (n + 1)n(n − 1) is 3! = 3*2*1 is true.
n = 1 then (n + 1)! = (n + 1)n(n − 1) is 2! = 2*1*0 is false.
n = 0 then (n + 1)! = (n + 1)n(n − 1) is 1! = 1*0*-1 is false.
n = -1 then (n + 1)! = (n + 1)n(n − 1) is 0! = 0*-1*-2 is false.